BORDER POROUSNESS AND THE FULANI HERDSMEN VIOLENCE AS THREAT TO NIGERIA’S NATIONAL SECURITY (2013-2022): IMPLICATION FOR THE ATTAINMENT OF SDG GOAL 16 (PEACE) - Segun Joshua; Adekunle Olanrewaju; Jeremiah Etuk (International Studies Journal)
Nigeria as a country is plagued with numerous problems of insecurity. This study examines border porousness, Nigeria’s national security and violence perpetrated by the Fulani herdsmen and its implication for attaining sustainable development goal 16 (peace). Relying on the fragile state theory, backed by secondary methods of data collection, the study investigates the challenges of securing the nation’s borders and how the activities of the herdsmen directly affect the national security of the Nigerian state with negative impact on sustainable development goal 16 (peace). Findings from the study reveal that the numerous illegal border routes in the country and the weak security system pave the way for illegal migrants. Their activities are inimical to the attainment of sustainable development goal 16 (peace). The study recommends proper border monitoring and establishment of ranches for herders and a pre-emptive approach to security management in the country.